Frequency of Retinal Vein Occlusion (RVO) and its Association with Hypertension by Variability of Retinal Hemorrhages at Fundoscopy after Retinal Vein Occlusion in Patients with Hypertension (Medical Forum Monthly, 2021)
Objective: To find out the frequency of RVO and its association with hypertension by variability of retinal hemorrhages at fundoscopy after retinal vein occlusion in patients with hypertension.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Sindh Institute of Eye Hospital, Hyderabad from 28 December 2019 to 15 May 2019.Materials and Methods: This study was performed on 89 patients in the age of >30 years < 70 years, and recently diagnosed central retinal occlusion cases were included. Hypertension diagnosis was confirmed and 89 patients were treated at the age of 35 years. By careful exam of the fundus of 90 D Volk Lens on Slit Lamp and fundus photography. The researchers initiated their work and an experienced ophthalmologist verified their final diagnosis. Statistical package for social science version 20 was used to analyze data.Results: A total of 89 patients who have hypertension with retinal vein occlusion (RVO) have received fundoscopy. We discovered that age (OR =1.72, 95 percent CI: 1.27–2.34), hypertension (OR =2.56, 95 percent CI: 1.31–5.08), stroke history (OR =2.08, 95 percent CI: 1.01–4.45), and hypercholesterolemia (OR =1.84, 95 percent CI: 1.01–3.35) were significantly associated with RVO. Uncontrolled hypertension (OR =3.46, 95 percent CI: 1.72–6.94) and un-medicated hypertension (OR = 4.12, 95 percent CI: 2.01–8.46) were significantly linked with RVO in a sample of hypertensive patients.Conclusion: Hypertension, a particularly modifiable risk factor, was the most strongly associated factor for RVO in our study.